2015
DOI: 10.1264/jsme2.me15080
|View full text |Cite
|
Sign up to set email alerts
|

The Type III Secretion System (T3SS) is a Determinant for Rice-Endophyte Colonization by Non-Photosynthetic <i>Bradyrhizobium</i>

Abstract: Plant associations by bradyrhizobia have been detected not only in leguminous plants, but also in non-leguminous species including rice. Bradyrhizobium sp. SUTN9-2 was isolated from Aeschynomene americana L., which is a leguminous weed found in the rice fields of Thailand. This strain promoted the highest total rice (Oryza sativa L. cultivar Pathum Thani 1) dry weight among the endophytic bradyrhizobial strains tested, and was, thus, employed for the further characterization of rice-Bradyrhizobium interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
62
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 39 publications
2
62
0
Order By: Relevance
“…T3SSs deliver T3Es directly into the extracellular environment or into the cytosol of eukaryotic host cells (Cornelis & Van Gijsegem, 2000;He, Nomura, & Whittam, 2004;Pallen, Chaudhuri, & Henderson, 2003). Previous reports showed that T3SSs may have either positive or negative effects on leguminous plant-rhizobia symbiosis (Freiberg et al, 1997;Hueck, 1998;Okazaki et al, 2010;Piromyou et al, 2015;Skorpil et al, 2005). Moreover, the T3SS of Sinorhizobium fredii NGR234 is functional and is involved in the determination of the host range of nodulation (Viprey, Greco, Golinowski, Broughton, & Perret, 1998).…”
mentioning
confidence: 99%
“…T3SSs deliver T3Es directly into the extracellular environment or into the cytosol of eukaryotic host cells (Cornelis & Van Gijsegem, 2000;He, Nomura, & Whittam, 2004;Pallen, Chaudhuri, & Henderson, 2003). Previous reports showed that T3SSs may have either positive or negative effects on leguminous plant-rhizobia symbiosis (Freiberg et al, 1997;Hueck, 1998;Okazaki et al, 2010;Piromyou et al, 2015;Skorpil et al, 2005). Moreover, the T3SS of Sinorhizobium fredii NGR234 is functional and is involved in the determination of the host range of nodulation (Viprey, Greco, Golinowski, Broughton, & Perret, 1998).…”
mentioning
confidence: 99%
“…Motility, chemotaxis, production of cell-wall degrading products and lipopolysaccharide formation are among the observed traits for bacteria to infect and adapt to inside plants (Piromyou et al, 2015). Comparative genomic or metagenomic analyses together with mutational studies have confirmed the importance of these traits.…”
Section: Traits For Successful Invasion Colonization and Translocatimentioning
confidence: 98%
“…SUTN9-2, which originally formed symbiotic relationships with the leguminous weed Aeschynomene americana (Piromyou et al, 2015). Pectinesterase expression in this bacterium was up-regulated after being inoculated on rice seedlings (Piromyou et al, 2015). In addition to the abovementioned traits, Kost et al (2014) found that oxalotrophy, the capacity of utilizing oxalate as a carbon source, is required for the successful colonization of B. phytofirmans PsJN on lupin and maize plants.…”
Section: Traits For Successful Invasion Colonization and Translocatimentioning
confidence: 99%
See 2 more Smart Citations